The mental health, quality of life and life satisfaction of internally displaced persons living in Nakuru County, Kenya: a critique - Robson Mandishekwa (BMC, 2021)
Abstract The study titled '[t] he mental health, quality of life and life satisfaction of internally displaced persons living in Nakuru County, Kenya' by Getanda, Papadopoulos and Evans identifies a critical area and contributed significantly to literature. Despite the contribution, there are some issues in that study that deserve attention. For example, the use of the satisfaction with life scale instead of the temporal satisfaction with life scale, for a pre-and post-displacement study, is questionable. It is important to note that the scores from the satisfaction with life scale can only measure life satisfaction at a particular point while the temporal satisfaction with life can be used to determine life satisfaction between pre-and post-displacement periods. Again, conflicting statements in the abstract and methods sections have been noted, where the abstract refers to refugee camps while methods refer to internally displaced persons' camps. Finally, some reported statistics have been found to have errors. It is important to highlight these critical issues to readers for a better understanding. This study, therefore, endeavours to critique that study and clarify some of these issues so that readers get better understandings. Recommendations for future studies are made.